Clinical outcomes of dose modification during pirfenidone treatment for IPF: A nationwide post-marketing surveillance study - Kang, Jieun; Chung, Man Pyo; Park, Moo Suk; Oh, In Jae; Lee, Heung Bum; Kim, Young Whan; Park, Jong Sun; Uh, Soo Taek; Kim, Yun Seong; Jegal, Yangjin; Song, Jin Woo (Frontiers in Pharmacology, 2023)
Background: Pirfenidone, an antifibrotic medication approved for the treatment of idiopathic pulmonary fibrosis (IPF), often requires dose reduction owing to adverse events. In this study, we evaluated if pirfenidone’s reduced dose has any impact on clinical outcomes in patients with IPF. Methods: We used the data of a prospective post-marketing study of pirfenidone conducted at 10 hospitals in South Korea from 2014 to 2017. Dose reduction was defined when the pirfenidone dose was temporarily or permanently reduced to manage adverse events or when the treatment dose failed to reach the standard dose. Study patients were classified based on the most frequently administered dose during 48-week follow-up—1800 mg, 1200 mg, and <1200 mg/day. The following clinical outcomes were compared between the groups: death, hospitalization, acute exacerbation, pulmonary function decline, and changes in severity of dyspnea and cough. Results: The median follow-up duration in all 143 patients was 11 months. During the study period, 70.6% experienced at least one dose reduction. Patients treated with standard-dose pirfenidone tended to be young and had the lowest diffusing capacity. Pulmonary function changes did not differ depending on the pirfenidone dose. The three groups were not significantly different in terms of the proportion of death, hospitalization, and acute exacerbation. The symptom changes were also similar between the groups. Conclusions: Reduced doses did not negatively impact clinical outcomes compared with the standard-dose pirfenidone in patients with IPF. Dose reduction may be a useful method to manage adverse events while maintaining therapeutic efficacy.